Eksplorasi Metode Tafsir bi Al-Ra'yi dalam Surah al-Ma'un pada Kitab Tafsir al-Azhar - Syahruddin, Siti Masyita; Abubakar, Achmad; Irham , Muhammad; Mahmudah, Mahmudah; Mi’rat, Muhammad (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
This study examines about tafsir bi al-ra'yi method in Surah al-Ma'un in the Tafsir al-Azhar, authored by Buya Hamka. This research is a library-based study using a descriptive-analytical approach aimed at understanding tafsir bi al-ra'yi method applied by Buya Hamka in Surah al-Ma'un and its relevance to contemporary social contexts. The results show that the use of tafsir bi al-ra'yi in Surah al-Ma’un is demonstrated through logical explanations, Buya Hamka’s interpretations that refer to previous mufassir, and he also uses reasoning and humanitarian perspective. The relevance of interpreting Surah al-Ma'un in the current social context includes care for orphans and the poor, opposition to hypocrisy in religion, and an emphasis on social responsibility. This study aims to give the positive impact towards society by helping them to understand and apply Islamic teachings in their daily lives more effectively and meaningfully, particularly through relevant and dynamic interpretations in relation to the social context.